Exposure characteristics of ferric oxide nanoparticles released during activities for manufacturing ferric oxide nanomaterials. (February 2015) - Xing, Mingluan; Zhang, Yuanbao; Zou, Hua; Quan, Changjian; Chang, Bing; Tang, Shichuan; Zhang, Meibian
Abstract The exposure characteristics of Fe2O3 nanoparticles (NPs) released in a factory were investigated, as exposure data on this type of NP is absent. The nature of the particles was identified in terms of their concentrations [i.e. number concentration (NC20–1000 nm), mass concentration (MC100–1000 nm), surface area concentration (SAC10–1000 nm)], size distribution, morphology and elemental composition. The relationships between different exposure metrics were determined through analyses of exposure ranking (ER), concentration ratios (CR), correlation coefficients and shapes of the particle concentration curves. Work activities such as powder screening, material feeding and packaging generated higher levels of NPs as compared to those of background particles (p < 0.01). The airborne Fe2O3 NPs exhibited a unimodal size distribution and a spindle-like morphology and consisted predominantly of the elements O and Fe. Periodic and activity-related characteristics were noticed in the temporal variations in NC20–1000 nm and SAC10–1000 nm. The modal size of the Fe2O3 NPs remained relatively constant (ranging from 10 to 15 nm) during the working periods. The ER, CR values and the shapes of NC20–1000 nm and SAC10–1000 nm curves were similar; however, these were significantly different from those for MC100–1000 nm. There was a high correlation between NC20–1000 nm and SAC10–1000 nm, and relatively lower correlations between the two and MC100–1000 nm. These findings suggest that the work activities during the manufacturing processes generated high levels of primary Fe2O3 NPs. The particle concentrations exhibited periodicity and were activity dependent. The number and SACs were found to be much more relevant metrics for characterizing NPs than was the mass concentration.